A short guide to the legislative procedure in the European Union - Cabral, Tiago Sérgio (2020)
This paper aims to clarify how the legislative procedure works in the European Union (hereinafter, EU), both in the Treaties and in practice. We will study the rules governing the ordinary legislative procedure and the special consent and consultation procedures. Advantages and shortcomings of each of the procedures will also be addressed, including the main actors and the level of transparency and accountability. Within the ordinary legislative procedure, we will assess whether the informal trilogues should be reformed to be more accessible to the European citizen. Lastly, our paper will also address the use of passerelle clauses and citizen’s and how they can affect the lawmaking procedure in the EU